2012
DOI: 10.5552/drind.2012.1128
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability of Kitchen Furniture for Elderly People in Terms of Safety

Abstract: • The number of senior citizens is rapidly increasing, which consequently signifi es an increase in the number of people having sight, hearing or memory diffi culties, people with hampered mobility, and people who fi nd it increasingly diffi cult to process information. Elderly persons experience a greater degree of risk whilst performing daily tasks in their kitchens. Moreover, they are more susceptible to infection and illnesses, necessitating greater care to achieve hygienic conditions within their kitchens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
1
7
0
6
Order By: Relevance
“…In their domestic settings, most of the problems that the elderly and disabled people encounter are found in those areas where enhanced activity is required, such as the bathroom and kitchen (Fabisiak & Kłos, ; Hrovatin, Širok, Jevšnik, Oblak, & Berginc, ; Kirvesoja, Väyrynen, & Häikiö, ; Sydor, ; Sydor, Wiaderek, Fabisiak, & Kłos, ). Designing interior and kitchen furniture, then, plays an important role in providing a comfortable and safe home environment (Bonenberg, ; Fabisiak & Kłos, ).…”
Section: Motor Impairment and Kitchen Furniture Designmentioning
confidence: 99%
“…In their domestic settings, most of the problems that the elderly and disabled people encounter are found in those areas where enhanced activity is required, such as the bathroom and kitchen (Fabisiak & Kłos, ; Hrovatin, Širok, Jevšnik, Oblak, & Berginc, ; Kirvesoja, Väyrynen, & Häikiö, ; Sydor, ; Sydor, Wiaderek, Fabisiak, & Kłos, ). Designing interior and kitchen furniture, then, plays an important role in providing a comfortable and safe home environment (Bonenberg, ; Fabisiak & Kłos, ).…”
Section: Motor Impairment and Kitchen Furniture Designmentioning
confidence: 99%
“…Similarly as in other European countries, also in Poland the mean life span increased from 40 years in 1900 to approx. 80 in 2000 (Lewandowski, 2000), and consequently the number of people suffering from different forms of disability is also increasing (Freedman and Martin, 1998;Hrovatin et al, 2012). Literature data report that in the year 1988 every tenth inhabitant of Poland was classified as disabled (Kowal, 2002).…”
Section: Uvodmentioning
confidence: 99%
“…Respondents pointed to the necessity of replacing traditional doors with a vertical axis of rotation with sliding doors in order to completely eliminate the risk of a bump (9 %) as well as replacing standard handles with recessed handles (7 %). The need for arranging the kitchen with furniture without handles and equipped with sliding doors was also highlighted by Hrovatin et al (2012). The respondents would like to have induction cook tops in their kitchens; however, instead of sensory control they should have manual control (e.g.…”
Section: Rezultat I Raspravamentioning
confidence: 99%
See 1 more Smart Citation
“…The project team developed new design concepts for kitchen lines, as well as devices for physical It has been found that there is no other publication within the available literature that presents research into the design work for kitchens produced for the elderly and people with motor impairment, which simultaneously uses traditional and environmental design methods. There are publications that refer to the design of bespoke kitchen lines for elderly and/or disabled people (e.g., [35][36][37][38][39][40][41]), but none of them consider the environmental aspects of the respective processes. On the other hand, there are publications that deal with kitchen eco-design but without any specific consideration of the needs of elderly and/or disabled people, e.g., [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%